Does Postmodernism Really Entail a Disregard for the Truth? Similarities and Differences in Postmodern and Critical Rationalist Conceptualizations of Truth, Progress, and Empirical Research Methods - Holtz, Peter (Frontiers in Psychology, 2020)
Within this article, I will compare postmodernist and critical rationalist conceptualizations of epistemological key concepts such as truth, progress, and research methods. An analysis of Gergen’s program for a postmodern psychology shows that a naïve positivist understanding of truth is clearly incompatible with his postmodernist approach, whereas a correctly understood falsificationist use of truth as a guiding ideal may not be. However, postmodernists are often content with a diversity of voices as the endpoint of scientific activities, whereas critical rationalists such as Popper would put more emphasis on attempts to reach a common understanding. The differences between critical rationalists such as Popper and Deutsch and postmodernists such as Gergen are more complicated when it comes to conceptualizations of progress: Whereas postmodernists do not deny the existence of some forms of progress such as technological innovation, they argue that the modernist grand narrative, which views Western culture and the corresponding technological revolutions as being equal to epistemological and societal and political progress per se, has become untenable. Debates on possible negative consequences of modern technology are one example of evidence for this. Here, critical rationalists tend to engage in a legitimization discourse sensu Lyotard and to defend Western culture with all its deficiencies as a necessary precondition for evolutionary epistemic as well as societal and political progress, although they would agree with large parts of the postmodern critique of modernism. Postmodernists and critical rationalists would both agree that psychology as a field would benefit greatly, among other things, from a transition from a methods-oriented approach to scientific knowledge to a more problem-oriented approach, and from less methodological dogmatism. Taken together, postmodernism and critical rationalism may not be as irreconcilable as it may seem at first glance.